Pengaruh Pengetahuan Pajak, Sosialisasi Pajak dan Sanksi Pajak, Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus: Samsat Lubuk Sikaping) - Kholbi, Nurainun; Situngkir, Anggiat (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research examines how Tax Knowledge, Tax Socialization, and Tax Sanctions affect Lubuk Suhuing Samsat Office motor vehicle tax payer compliance. Examining the characteristics that promote taxpayer compliance is crucial to improving regional tax income. This quantitative research surveys 100 Lubuk Suhuing Samsat taxpayers using questionnaires. The data were analyzed using SPSS linear multiple regression. In this research, Tax Knowledge, Tax Socialization, and Tax Sanctions are independent variables while Taxpayer Compliance is dependent. The findings reveal that three independent factors concurrently affect taxpayer compliance. Tax Knowledge, Tax Socialization, and Tax Sanctions positively and significantly affect Taxpayer Compliance. To guarantee long-term success, strong communication and unpaid education initiatives are also crucial. This research demonstrates that enhancing Samsat office service quality may increase taxpayer trust and volunteer attitudes. Better local government-community partnership should also make environmental taxes more transparent and beneficial.